2007
DOI: 10.1002/bit.21724
|View full text |Cite
|
Sign up to set email alerts
|

Conformational flexibility of a model protein upon immobilization on self‐assembled monolayers

Abstract: The present study reports on the retention of conformational flexibility of a model allosteric protein upon immobilization on self-assembled monolayers (SAMs) on gold. Organothiolated SAMs of different compositions were utilized for adsorptive and covalent attachment of bovine liver glutamate dehydrogenase (GDH), a well-characterized allosteric enzyme. Sensitive fluorimetric assays were developed to determine immobilization capacity, specific activity, and allosteric properties of the immobilized preparations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
4
0
1
Order By: Relevance
“…The effect of conformational flexibility on the enzyme activity was initially justified by the observation that enzyme immobilized on a carrier via a suitable spacer often resulted in better retention of activity than the enzyme immobilized without a spacer [163166]. Bigdeli et al (2008) reported the retention of conformational flexibility of glutamate dehydrogenase, used as a model allosteric protein, upon its immobilization on self-assembled monolayers-modified gold [167]. …”
Section: Immobilization To Upgrade Industrial Enzymesmentioning
confidence: 99%
“…The effect of conformational flexibility on the enzyme activity was initially justified by the observation that enzyme immobilized on a carrier via a suitable spacer often resulted in better retention of activity than the enzyme immobilized without a spacer [163166]. Bigdeli et al (2008) reported the retention of conformational flexibility of glutamate dehydrogenase, used as a model allosteric protein, upon its immobilization on self-assembled monolayers-modified gold [167]. …”
Section: Immobilization To Upgrade Industrial Enzymesmentioning
confidence: 99%
“…These fine effects are conveyed throughout the protein structure via subtle local conformational changes that are brought by the presence of specific ligands; in other words, it is the environment of the allosteric protein that is regulating its function [85]. Allostery may be an intrinsic property of all proteins [86], and structural flexibility is important for all protein functions [87].…”
Section: Effect Of Ligandsmentioning
confidence: 99%
“…Γ ≫ 1 without pair contribution Although it has been less studied than its like-charge counterpart [1][2][3], the behaviour of two interacting oppositely charged mesoscopic bodies in solution is of importance in various contexts, including colloid physics [4][5][6][7][8], biochemistry related experiment interpretations [9,10], drug design [11], and structural biology [12]. The simple system of two charged plates with opposite uniform surface charges represents a model of choice that enables one to get analytical results in some limits, and furthermore, that provides a starting point to estimate the interaction energy between two colloids of various geometry [13,14].…”
Section: Introductionmentioning
confidence: 99%